Early player transition in elite youth and first team soccer: The predictive role of sprint distance and high-intensity acceleration and deceleration attributes - McGuigan, M.; Dello Iacono, A.; McRobert, A.; Cowan, D.; Unnithan, V. B. (International Journal of Sports Science & Coaching, 2024)
Physical performance is an important determinant of elite youth soccer player development and can influence successful transition through the professional phase of the talent development pathway. In response to previous research highlighting key stakeholders` perceptions that successful transitions within the club pathway are influenced by sprinting capacity and explosive power; this study objectively quantified the predictive value of sprint distance and high intensity acceleration and deceleration efforts on the early transition of elite, professional youth soccer players from U18 to U21, and U21 to first team squads of a Scottish Premier League club. Early transition was defined as a player progressing to the next age group (i.e., U18 to U21) prior to reaching the chronological age limits of his current squad. Retrospective physical performance data of thirty-seven players from training and competitive matches across two seasons were analysed. Results suggest that early transition is less likely for players progressing from the U21 to the first team relative to players progressing from U18 to U21. Relative sprint distance resulted in a 52% probability of early transition (OR = 0.52) with relative aggregated high intensity acceleration and deceleration efforts reflecting an increased probability of early transition (OR = 1.70) for elite youth soccer players within the club. This novel study provides a unique insight to the complexities and context-specific nature of youth soccer player development and transition. This paper challenges the subjective perceptions of key stakeholders using objective physical data of youth players who have transitioned to advanced squads.